PERSEPSI ORANG TUA TERHADAP PENDIDIKAN SEKS ANAK USIADINI PADA SISWA KELAS B DI TK ISLAM SAKINAH - Anriani, Echy; Alucyana, Alucyana (UIR PRESS, 2024)
This study aims to determine parents' perceptions of early childhood sex education in class B students of Sakinah Islamic Kindergarten, and relate it to theories about parents' views, interpretations and assessments of early childhood sex education in class B students of Sakinah Islamic Kindergarten. Therefore, this study was conducted to determine parents' perceptions of early childhood sex education in class B students at Sakinah Islamic Kindergarten. This study uses a descriptive narrative qualitative research approach. Data collection techniques in this study are observation, interviews, and documentation. While the data analysis techniques used in this study are data reduction, data presentation, and drawing conclusions. The results of this study indicate that parents' views of sex education for early childhood are seen only as limited to the relationship between people who are already married or the relationship between husband and wife. Parents' interpretation of early childhood sex education is to provide understanding to children about which parts of the body are allowed to be touched, as well as to provide understanding to children about differences in male and female body parts. Parents' assessment of early childhood sex education is that they disagree about the existence of sex education for early childhood, because it is considered an unnatural thing if it is applied too early.